Demographic population structure of black howler monkeys in fragmented and continuous forest in Chiapas, Mexico: Implications for conservation. Issue 8 (30th June 2020) - Klass, Keren; Van Belle, Sarie; Estrada, Alejandro
Abstract: For wild primates, demography studies are increasingly recognized as necessary for assessing the viability of vulnerable populations experiencing rapid environmental change. In particular, anthropogenic changes such as habitat loss and fragmentation can cause ecological and behavioral changes in small, isolated populations, which may, over time, alter population density and demographic structure (age/sex classes and group composition) in fragment populations relative to continuous forest populations. We compared our study population of Endangered black howler monkeys ( Alouatta pigra ) in 34 forest fragments around Palenque National Park (PNP), Mexico (62 groups, 407 individuals), to the adjacent population in PNP, protected primary forest (21 groups, 134 individuals), and to previous research on black howlers in fragments in our study area (18 groups, 115 individuals). We used χ 2 and Mann–Whitney U tests to address the questions: (a) what is the current black howler demographic population structure in unprotected forest fragments around PNP? (b) How does it compare to PNP's stable, continuous population? (c) How has it changed over time? Compared to the PNP population, the fragment populations showed higher density, a significantly lower proportion of multimale groups, and significantly fewer adult males per group. The population's age/sex structure in the fragmented landscape has been stable over the last 17 years, but differed in a higher proportion of multifemale groups, higher density, and higher patch occupancy in the present. In the context of conservation, some of our results may be positive as they indicate possible population growth over time. However, long‐term scarcity of adult males in fragments and associated effects on population demographic structure might be cause for concern, in that it may affect gene flow and genetic diversity. The scarcity of adult males might stem from males experiencing increased mortality while dispersing in the fragmented landscape, whereas females might be becoming more philopatric in fragments. Abstract : Adult male black howler monkey in secondary growth at the edge of a forest fragment. Research Highlights: Fewer adult male black howler monkeys were present in the fragmented landscape compared to the population in the adjacent continuous forest in Palenque National Park (PNP). The population in forest fragments has maintained a largely stable composition over the last 17 years, although density and patch occupancy in the fragmented landscape have increased. Results indicate both possible population growth in the fragmented landscape, and differences in population demographic structure relative to PNP, with potential consequences for future population viability in forest fragments.